Finding a voice through research (2006)
One question guided this experimental study: What impact does the change from teacher training to educational research have on university teachers' methodology and attitudes to teaching? To find answers to this question, the researchers selected five teachers of English as a Foreign Language (EFL) at the language centre of a private university on the Caribbean Coast of Colombia and instructed them in the principles and procedures of action research. Semi-structured interviews were then conducted with each of the teachers involved, a focus group with students and class observations, and field notes were made. Most data sources were audio-taped and transcribed, and all were coded and analysed using qualitative methods. Results indicate that by carrying out research, these teachers, who find it very hard to make ends meet, were able to find a voice, articulate their ideas and propose new ways of teaching. They also found ways to see things differently, from a humanistic angle, and to empower themselves. Copyright © 2006, SAGE Publications.